BLACAT1 predicts poor prognosis and serves as oncogenic lncRNA in small‐cell lung cancer. Issue 2 (11th September 2018) - Chen, Weiwei; Hang, Ye; Xu, Weiwei; Wu, Jixiang; Chen, Longyun; Chen, Jinzhong; Mao, Yixiang; Song, Jin; Song, Jianxiang; Wang, Hanhua
Abstract: Bladder cancer‐associated transcript 1 (BLACAT1) is a novel identified long noncoding RNA (lncRNA) in bladder cancer, and has been suggested to function as an oncogenic lncRNA in several types of human cancer. However, its involvement in the progression of small‐cell lung cancer (SCLC) remained unknown. The aim of our study was to investigate the clinical value and biological function in SCLC. In our results, BLACAT1 expression was increased in SCLC tissues and cell lines compared with paired adjacent normal tissues and bronchial epithelial cell lines, respectively. In addition, BLACAT1 high‐expression was obviously associated with advanced clinical stage, large tumor size, more lymph node metastasis, present distant metastasis, and poor prognosis. Furthermore, multivariate analysis indicated that high‐expression of BLACAT1 acted as an independent poor prognostic factor for overall survival in SCLC cases. The loss‐of‐function studies suggested that of BLACAT1 suppressed SCLC cell proliferation, migration, and invasion, and induced G0/G1 phase arrest. In conclusion, BLACAT1 is associated with the malignant status and prognosis in patients with SCLC, and functions as an oncogenic lncRNA in regulating cell proliferation and motility, suggesting BLACAT1 may act as a potential target for SCLC prevention and treatment. Abstract : Bladder cancer‐associated transcript 1 (BLACAT1) is associated with the malignant status and prognosis in patients with small‐cell lung cancer (SCLC), and functions as an oncogenic long noncoding RNA in regulating cell proliferation and motility, suggesting BLACAT1 may act as a potential target for SCLC prevention and treatment